Organizational Strategy: An Ecological Perspective - Boeker, Warren (Academy of Management Journal, 1991)
This study demonstrates the application of theories and models from organizational ecology to the study of organizational strategy. Competition between strategic groups and the effects of environmental characteristics are estimated for an 18-year period in the U.S. brewing industry. Results indicate that both competitive and symbiotic relationships exist between strategic groups and that environmental characteristics have an important influence on strategic viability. Ecological arguments are developed to explain the role of competition and environment in influencing the expansion and decline of organizations pursuing different strategies.